Four mice deep in the jungle - Stilton, Gern̤imo. (New York : Scholastic, 2004)
I have never been a brave mouse, but lately, my fears were taking over my life! So Thea and Trap decided to cure me by dragging me all the way to the jungle, where I was forced to eat bug soup, swim in raging rivers, and even wrangle snakes! How would a 'fraidy mouse like me ever survive?
RL3.
007-010.
460
Accelerated Reader AR
Keywords: Mice -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Juvenile fiction